Coverage, Access, and Affordability under Health Reform: Learning from the Massachusetts Model - Sharon K. Long; Karen Stockley; Kate Willrich Nordahl (SAGE Publishing, 2012)
While the impacts of the Affordable Care Act will vary across the states given their different circumstances, Massachusetts' 2006 reform initiative, the template for national reform, provides a preview of the potential gains in insurance coverage, access to and use of care, and health care affordability for the rest of the nation. Under reform, uninsurance in Massachusetts dropped by more than 50%, due, in part, to an increase in employer-sponsored coverage. Gains in health care access and affordability were widespread, including a 28% decline in unmet need for doctor care and a 38% decline in high out-of-pocket costs.